Proceedings of Offshore Technology Conference 2009
DOI: 10.4043/otc-19904-ms
|View full text |Cite
|
Sign up to set email alerts
|

Flow Induced Pulsations due to Flexible Risers

Abstract: Flexible rough bore pipes are widely used in the oil and gas industry. One application is their use as risers and jumpers for gas production, transport and injection. In the past, some flexible pipes have been experiencing high amplitude tonal pressure fluctuations above critical velocities. These pulsations can cause mechanical vibrations at topside and subsea platforms, resulting eventually in topside/subsea piping failures [Swindell 2007].A Joint Industry Project, sponsored by BP, Bureau Veritas, ExxonMobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
Order By: Relevance
“…Small fractions of liquid are known to eliminate the singing, as was first reported for corrugated pipes by Belfroid (2009). Small fractions of liquid are known to eliminate the singing, as was first reported for corrugated pipes by Belfroid (2009).…”
Section: Mitigation Of Singing By Liquid Injectionmentioning
confidence: 68%
See 1 more Smart Citation
“…Small fractions of liquid are known to eliminate the singing, as was first reported for corrugated pipes by Belfroid (2009). Small fractions of liquid are known to eliminate the singing, as was first reported for corrugated pipes by Belfroid (2009).…”
Section: Mitigation Of Singing By Liquid Injectionmentioning
confidence: 68%
“…Detailed results can be found in for instance Belfroid (2009), Swindell (2007), Nakiboglu (2011Nakiboglu ( , 2012aNakiboglu ( , 2012b, . Specifically, the frequency content, the onset velocity and amplitude of the pulsations are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Long flexible pipes necessary for conveying gas are corrugated on the inside and are known to exhibit strong sound levels of pure tones at some offshore installations. A study directly treating the singing riser problem was recently published by Belfroid et al 6 Using a simple experimental arrangement, the authors of the present communication found that the addition of a low frequency oscillation significantly influences the flow-excited whistling in a short corrugated pipe. Moreover, it was found that the whistling could be silenced or moved to higher frequencies, and also that the low frequency oscillation itself may excite whistling at the frequencies corresponding to the pipe's longitudinal modes.…”
Section: Introductionmentioning
confidence: 89%
“…(2) Pressure of the bore fluids, and the hydrostatic pressure, externally and within the annulus (3) Extreme/ survival loading, influenced by e.g. vessel motions, metocean conditions, marine growth, soil conditions (4) Variable loading: fatigue (5) Product fluid composition and the partial pressures of harmful constituents (6) Corrosion, linked to a.o. (1), (2), (5) (7)…”
Section: !"#$%And'()*+and(%#mentioning
confidence: 99%